Incidencia de la dinámica del comercio exterior de las Zonas Francas en el PIB colombiano entre el periodo 2010-2020 (2022)
The performance of FTZs exports and imports was studied according to their behavior within the GDP, in order to answer the question intended to validate out, what is the incidence of exports and imports of FTZs in the Colombian GDP, taking as a reference the period 2010-2020?. Therefore, the research was conducted under a quantitative type of study with a correlational scope that is supported by public statistical sources. In this way, a multiple linear econometric model in natural logarithm without constant was estimated, showing that the GDP and the exports and imports carried out in the FTZs present a statistically significant relationship, giving way to a discussion that exposes the positive and negative factors of these spaces, seeking to propose an idea that improves the position of the FTZs by expanding their eventual future contribution within the national GDP.